Common Ground in Demonstrative Reference: The Case of Mano (Mande) - Khachaturyan, Maria (Frontiers in Psychology, 2020)
That demonstratives often have endophoric functions marking referents outside the physical space of interaction accessible through cognition, especially memory, is well known. However, these functions are often classified as independent from exophoric ones and are typically seen as secondary with respect to spatial deixis. However, data from multiple languages shows that cognitive access to referents functions alongside with perceptual access, including vision. Cognitive access is enabled by prior interactions and prior familiarity with the referents. As a result of such interactions, the interlocutors share a great deal of knowledge about the referents which allows them locate even invisible objects but also facilitates reference to objects in the interactive field. Thus, in some languages, exophoric uses are not opposed to, but become routinely merged with endophoric ones and perceptual access gets merged with cognitive access. I illustrate this idea throughout the paper by using first-hand data from Mano. Adding another argument in favor of viewing demonstrative reference as a social, interactive process, the Mano data pushes the idea of salience of non-spatial parameters further and emphasized the importance of long-term interactional history both for the choice of demonstratives in exophoric reference and for the encoded distinctions in the demonstrative paradigm.